2010
DOI: 10.1063/1.3478836
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature dependence of the key electro-optical characteristics for midinfrared emitting quantum cascade lasers

Abstract: The equations for threshold-current density Jth, differential quantum efficiency ηd, and maximum wallplug efficiency ηwp,max for quantum-cascade lasers (QCLs) are modified for electron leakage and backfilling. A thermal-excitation model of “hot” injected electrons from the upper laser state to upper active-region states is used to calculate leakage currents. The calculated characteristic temperature T0 for Jth is found to agree well with experiment for both conventional and deep-well (DW) QCLs. For conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 13 publications
0
64
0
Order By: Relevance
“…The slope of the best linear fit yields T 0 = 199 K; the experiment gives 143 K. The discrepancy between between experiment and theory can be attributed to the omission of alloy, interface, and impurity scattering, and to lack of nonequilibrium phonons [25]. We note that a prior study [43] of the structure in [8], which employed rate equations, the effect of elastic scattering on lifetimes and electroluminescence linewidth, and upper-level electronic temperatures based on Vitiello et al's [44] measurement of the electron-lattice coupling constant on 4.8-µm-emitting conventional QCL, gave a T 0 value of 167 K. Figure 4 shows the subband electron temperatures (measuring the average in-plane kinetic energy of electrons in a subband, Equation (1e)) in the injector, upper lasing, and lower lasing levels, as a function of electric field for lattice temperatures of 160 K (left), 298 K (middle), and 378 K (right). Also shown is the weighted average electron temperature for a stage, with subband occupations acting as weights.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope of the best linear fit yields T 0 = 199 K; the experiment gives 143 K. The discrepancy between between experiment and theory can be attributed to the omission of alloy, interface, and impurity scattering, and to lack of nonequilibrium phonons [25]. We note that a prior study [43] of the structure in [8], which employed rate equations, the effect of elastic scattering on lifetimes and electroluminescence linewidth, and upper-level electronic temperatures based on Vitiello et al's [44] measurement of the electron-lattice coupling constant on 4.8-µm-emitting conventional QCL, gave a T 0 value of 167 K. Figure 4 shows the subband electron temperatures (measuring the average in-plane kinetic energy of electrons in a subband, Equation (1e)) in the injector, upper lasing, and lower lasing levels, as a function of electric field for lattice temperatures of 160 K (left), 298 K (middle), and 378 K (right). Also shown is the weighted average electron temperature for a stage, with subband occupations acting as weights.…”
Section: Resultsmentioning
confidence: 99%
“…Significant electron heating takes place: the weighted average electron temperature around the design field (∼ 80 kV/cm) is between 1000 and 1500 K. The injector and upper lasing levels are cooler than average, with electron temperatures between 400 K and 1000 K around the design field. These high electron temperatures in the upper lasing state will increase carrier leakage and impact the T 0 value [43]. The lower lasing level is considerably hotter than average, with electron temperatures in the range 2200 to 2400 K; the extractor states (not shown) have comparable temperatures to the lower lasing level.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, T 0 , the threshold-current density (J th ) characteristic temperature coefficient, and T 1 , the slope-efficiency (Z s ) characteristic temperature coefficient, have low values of $ 140 K [4,5]. This is a consequence of the fact that for conventional QCLs the core region is an SL structure composed of quantum wells (QWs) and barriers of fixed alloy compositions [4][5][6], and this constraint causes, for 4.5-5.0 mm-emitting devices, easy thermal excitation of electrons injected into the upper laser level to higher energy levels, and thus leads to loss of injected carriers [7]. We have shown that, by using the flexibility of MOVPE, one can perform two-dimensional (2-D) conduction-band engineering in the QCLs active regions (ARs) [3,[7][8][9] in order to suppress the electron leakage.…”
Section: Introductionmentioning
confidence: 98%
“…This is a consequence of the fact that for conventional QCLs the core region is an SL structure composed of quantum wells (QWs) and barriers of fixed alloy compositions [4][5][6], and this constraint causes, for 4.5-5.0 mm-emitting devices, easy thermal excitation of electrons injected into the upper laser level to higher energy levels, and thus leads to loss of injected carriers [7]. We have shown that, by using the flexibility of MOVPE, one can perform two-dimensional (2-D) conduction-band engineering in the QCLs active regions (ARs) [3,[7][8][9] in order to suppress the electron leakage. Specifically, the use of deep QWs in the ARs [7] and of barriers which vary in height across the ARs [8,9] was found to lead to significant increases in the energy differences between the upper laser level and higher-energy AR levels, thus substantially preventing thermal excitation and subsequent loss of the injected carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since typically the value of the ͑T eul / T͒ − 1 quantity is in the 0.15-0.20 range, 3 and E ul+1,ul Ͼ 1.5 ប LO , Eq. ͑1͒ is well approximated by the following:…”
mentioning
confidence: 99%